SOBRE EL HALLAZGO DE BIVALVOS DE AGUA DULCE (UNIONIDAE y MYCETOPODIDAE) EN EL TERCIARIO SUPERIOR DE EMPEDRADO, PROVINCIA DE CORRIENTES, ARGENTINA (Ameghiniana, 2013)
A faunule of naiades is described fram the Pliocene of Empedrado, Province of Corrientes, which should be forerunner of that inhabits the same region.